Human factors engineering and participatory design in the project of a nuclear research reactor control centre (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The Human Factors Engineering (HFE) program is an essential aspect for the design of nuclear installations. The overall aim of the HFE program is the improvement of the operational reliability and safety of plant operation. The HFE program main purpose is to ensure that human factor practices are incorporated into the plant design, emphasizing man-machine interface issues and design improvement of the nuclear reactor Control Centre. The Control Centre of nuclear reactor is a combination of control rooms, control suites and local control stations, which are functionally connected and located on the reactor site. The objective of this paper is to present a participatory design approach, including human factor issues, for the Control Centre of a nuclear research reactor used to produce radioisotopes and for nuclear research. The design approach is based on participatory design principles, using human factor standards, ergonomic guidelines, and the participation of a multidisciplinary team during all design phases. Using the information gathered, an initial sketch 3D of the Control Centre was developed.